Politik Uang dan Patronase dalam Pemilihan Kepala Desa (Pilkades) Cangakan Kecamatan Kasreman Kabupaten Ngawi Provinsi Jawa Timur Tahun 2013 - Deviria Arofatul Khusni; Nur Hidayat Sardini; Kushandayani - (Journal of Politic and Government Studies, 2018)
One of the village autonomy to organizing and managing its own in political and governmental area is realized by election activity to vote its own leader through head of village election (Pilkades). On Pilkades, there are political dynamics and local issues, such as money politics and patronage. On June 22nd 2013, Pilkades was held in Cangakan, Kasreman, Ngawi with two candidates. The purposes of this research are to identify mode of money politics that happened on Pilkades and to explain the formation of patronage between candidates and patron on Pilkades Cangakan that was held on 2013.The method used in this research is a qualitative research method with data collection techniques are interviews, literature study, and documentation. To determine the subject in this research used purposive sampling, snowball sampling, and random sampling. Primary information are obtained through in depth interview. Besides that, secondary information are obtained through head of Cangakan village office and Regent of Ngawi office.The study shows that there are some modes of money politics, they are: 1) Distributing cash to voters directly (vote buying, bribery, and preventing polls); 2) Distributing cash to voters indirectly (vote buying by a vote broker); 3) Distributing object to voters group directly (election bribery); and 4) Abuse of power by ijon politics. That money politics strategy indirectly had some correlation to the formation of patronage, because it generated the election cost so high. Patronage that created between candidates as clients and third actors as patron inconsequence of economic factor to covered their high cost candidacies. One of the candidate even became a client for some patron. The exchanged not only about money, but the client also mortgaged bengkok field (when he officially win the election) and made the voters as a commodities. Key Words  :  Money politics, Patronage, Pilkades